Emily Brady, Aesthetics of the Natural Environment - Stephens, Piers H.G. (Journal for the Study of Religion, Nature and Culture, 2004)
Emily Brady, Aesthetics of the Natural Environment (Edinburgh: Edinburgh University Press, 2003), pp.viii + 287. Paperback £16.99, ISBN 0 7486-1438 9. Hardback £49.99, ISBN 0-7486-1437 0.